2022
DOI: 10.4308/hjb.29.4.479-486
|View full text |Cite
|
Sign up to set email alerts
|

Gynura procumbens Adventitious Root Extract Altered Expression of Antioxidant Genes and Exert Hepatoprotective Effects Against Cadmium-Induced Oxidative Stress in Mice

Abstract: Exposure to cadmium (Cd) could increase of reactive oxygen species (ROS) and changes in  expression of antioxidant genes. Gynura procumbens is a medicinal plant that is rich in phenolic and flavonoid compounds. The aimed of study to evaluate the hepatoprotective effect of G. procumbens adventitious root (GAR) extract against Cd toxicity, especially expression rate of hepatic antioxidant genes. Twenty-five male mice were treated as follows: P1 (control), P2 (Cd100mg/L), P3 (GAR100mg/L + Cd100mg/L), P4 (GAR200mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Previous works have reported on the pharmaceutical activities of G. procumbens extract, especially their positive effect on human health (Takanashi et al 2019). Recent studies have shown that in vitro roots of G. procumbens have excellent antioxidant activity and hepatoprotective effects (Sugiharto et al 2021(Sugiharto et al , 2022. Furthermore, G. procumbens is a safe and edible plant because it does not contain toxic compounds like, pyrrolizidine alkaloids (Saiman et al 2012).…”
Section: H a Y At I H A Y At Imentioning
confidence: 99%
“…Previous works have reported on the pharmaceutical activities of G. procumbens extract, especially their positive effect on human health (Takanashi et al 2019). Recent studies have shown that in vitro roots of G. procumbens have excellent antioxidant activity and hepatoprotective effects (Sugiharto et al 2021(Sugiharto et al , 2022. Furthermore, G. procumbens is a safe and edible plant because it does not contain toxic compounds like, pyrrolizidine alkaloids (Saiman et al 2012).…”
Section: H a Y At I H A Y At Imentioning
confidence: 99%
“…For this reason, the Chinese name of this plant is "Pokok Sambung Nyawa," the meaning of which is "prolongation of life" [37,48]. Furthermore, certain findings have provided significant evidence demonstrating the promising hepatoprotective potentials of G. procumbens, which has piqued the interest of researchers to investigate further the protective effects of G. procumbens against specific types of hepatotoxicity [24,49]. Hence, the present study aims to evaluate the hepatoprotective activities of G. procumbens against CCl 4 -induced hepatotoxicity, and histopathological studies, and computationally predict the ADMET properties of its phytoconstituents.…”
Section: Introductionmentioning
confidence: 99%